Strategic Management of Madrasah Heads in Improving the Quality of Graduates at Madrasah Aliyah - Tsani Al Haqqi, I'in Sholikhus; Darim, Abu; Yaqin, Ainul (Journal of Education and Learning Innovation, 2025)
The objectives of this study are: first, to analyze the planning strategy of the madrasah head in improving the quality of graduates at MA. Unggulan Hikmatul Amanah.. Second, analyzing the implementation strategy of the madrasah head in improving the quality of graduates at MA. Unggulan Hikmatul Amanah.. Third, analyzing the evaluation strategy of the madrasah head in improving the quality of graduates at MA. Unggulan Hikmatul Amanah. Fourth, analyze the results of the madrasah principal's strategic management in improving the quality of graduates at MA. Unggulan Hikmatul Amanah.This research uses a case study research approach with a qualitative research type. Data were collected through interviews, documentation studies, and observation. Data analysis through the stages of data collection, data presentation, data reduction, and verification/conclusion drawing.The results of research is: first, the concept of the madrasah head planning strategy in improving the quality of graduates in MA. Unggulan Hikmatul Amanah are: a) translation and adjustment of the madrasah's vision and mission; b) transmitting graduation designation goals; c) determining targets; d) quality improvement programs for teachers and graduates; and e) internal and external analysis. Second, the concept of implementation strategies in improving the quality of graduates at MA. Unggulan Hikmatul Amanah. are: a) policy setting; b) involvement of all elements of the madrasah; c) determination of academic and non-academic programs; c) branding the characteristics and excellence of the madrasah; and d) cooperation with external parties. Third, the concept of evaluation strategies in improving the quality of graduates are: a) evaluation from external and internal parties; b) identification and SWOT analysis; and c) do not follow up. Fourth, the results of strategic management in improving the quality of graduates at MA. Unggulan Hikmatul Amanah are: a) the absorption of graduates in PTN and PTS, b) consistency of student learning outcomes, c) collaboration of academic curriculum and madrasah diniyah, d) student achievement results, and e) achievement development and improvement of teacher competence.